2021
DOI: 10.3390/md19090516
|View full text |Cite
|
Sign up to set email alerts
|

A Thermotolerant Marine Bacillus amyloliquefaciens S185 Producing Iturin A5 for Antifungal Activity against Fusarium oxysporum f. sp. cubense

Abstract: Fusarium wilt of banana (also known as Panama disease), is a severe fungal disease caused by soil-borne Fusarium oxysporum f. sp. cubense (Foc). In recent years, biocontrol strategies using antifungal microorganisms from various niches and their related bioactive compounds have been used to prevent and control Panama disease. Here, a thermotolerant marine strain S185 was identified as Bacillus amyloliquefaciens, displaying strong antifungal activity against Foc. The strain S185 possesses multiple plant growth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 75 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…Besides, W1 showed higher tolerance to a variety of proteases against F. oxysporum . These characteristics were better than the antifungal peptides produced by B. amyloliquefaciens S185, PT14, and B. velezensis HNAH 17806 ( Kim et al, 2015 ; Singh et al, 2021 ; Wang et al, 2021 ), indicating that W1 has superior application potential in the biocontrol of plant diseases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides, W1 showed higher tolerance to a variety of proteases against F. oxysporum . These characteristics were better than the antifungal peptides produced by B. amyloliquefaciens S185, PT14, and B. velezensis HNAH 17806 ( Kim et al, 2015 ; Singh et al, 2021 ; Wang et al, 2021 ), indicating that W1 has superior application potential in the biocontrol of plant diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Several isolates of B. amyloliquefaciens have exhibited their application potential as plant growth promoters, probiotics, and antibiotics. As effective candidates of biocontrol microorganisms in agriculture, B. amyloliquefaciens Pc3, S185, PT14, Rdx5, FZB42, and SWB16 suppressed the growth of many fungal or bacterial pathogens, such as A. longipes , C. gloeosporioides , and F. oxysporum ( Chen et al, 2009 ; Wang et al, 2014 ; Kim et al, 2015 ; Ding et al, 2019 ; Dong et al, 2019 ; Singh et al, 2021 ). B. amyloliquefaciens W0101 isolated here could suppress 9 pathogenic fungi, such as A. longipes , C. gloeosporioides , F. oxysporum , S. sclerotiorum , and P. amygdali , showing a broad spectrum of antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that CLPs from B. amyloliquefaciens DHA6 significantly inhibited mycelial growth and conidia germination of Fon ( Figure 4 ), providing mechanistic insights into the direct antifungal activity of B. amyloliquefaciens DHA6 against phytopathogenic fungi. Previous studies have reported that CLPs purified from different B. amyloliquefaciens strains, such as fengycins and iturins, inhibited mycelial growth and spore germination of Fo in vitro [ 21 , 22 , 23 , 63 , 64 ]. Iturins produced by Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Iturins family consists of a group of cyclic lipopeptides composed of a heptapeptide moiety and a chain of fatty acids linked by an α-amino bond. These are known for their strong antifungal activity against pathogenic yeasts and fungi [22,32,38].…”
Section: Introductionmentioning
confidence: 99%